Three Experimental Studies on Entrepreneurship - Ahmad Barirani (Copenhagen Business School (CBS), 2018)
Do entrepreneurs differ from others with regard to their behavioral traits, and can beliefs held by employers about these differences lead to self-employedworkers being stigmatized in the labor market? Although central to the study of entrepreneurship, the literature does not provide a clear answer to these questions. This can partly be due to the inherent difficulty in answering them by resorting to observational studies. People can select into entrepreneurship because of their preferences for the non-pecuniary benefits of the occupation, but also because of opportunities that (only) they perceive. Based on the premise that reliance on multiple methodological approaches can contribute to the credibility of empirical results, this thesis explores the above questions by resorting to experimental techniques. It first tests the hypothesis of whether entrepreneurs are more action-oriented than other occupational groups. Analyzing the playing strategies of 100s of entrepreneurs, managers and employees in an optimal stopping game suggests that entrepreneurs are indeed more action-oriented than others. It is theorized that this is driven by their lower levels of loss aversion and higher levels of curiosity. The empirical test results showthat (i) entrepreneurs score indeed higher, on average, than managers and employees on curiosity and lower on loss aversion; (ii) the difference in action-orientedness between entrepreneurs and others vanishes when controlling for individual curiosity levels and (iii) an alternative treatment that provides subjects with counterfactual information (about what would have happened in case of continuing) increases their willingness to stop. Under some assumptions, the combination of these results leads to the conclusion that the higher action-orientedness of entrepreneurs can be linked to their greater curiosity, but not to their lower level of loss aversion. These findings support the intuitive idea that (curiosity driven) action-orientedness enhances the identification and/or exploitation of opportunities.
hdl:10398/9612
Keywords: 650